2002
DOI: 10.2135/cropsci2002.6370
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Head Blight Reaction of Langdon Durum‐Triticum dicoccoides Chromosome Substitution Lines

Abstract: Fusarium head blight (FHB), caused by Fusarium graminearum Schwabe, is a serious disease problem on durum wheat (Triticum turgidum L. var. durum) in the USA. To date, the resistance to FHB available in hexaploid wheat (T. aestivum L.) sources has not been transferred successfully to tetraploid durum. In the 1980s, USDA geneticist L.R. Joppa produced a set of disomic lines [LDN(DIC)] derived from wild emmer (T. turgidum L. var. dicoccoides). Each line had a different pair of chromosomes from T. dicoccoides subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…Although Israel A per se is susceptible to FHB (Table 1; Stack et al, 2002a), the FHB resistance QTL on chromosome 3A is probably suppressed by one or more other genes present in the genomes of Israel A. Other research suggests that the suppressor gene is located on chromosome 2A (Stack et al, 2002a;Garvin et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Israel A per se is susceptible to FHB (Table 1; Stack et al, 2002a), the FHB resistance QTL on chromosome 3A is probably suppressed by one or more other genes present in the genomes of Israel A. Other research suggests that the suppressor gene is located on chromosome 2A (Stack et al, 2002a;Garvin et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Wheat lines with high levels of FHB resistance generally possess multiple resistance genes, which act in an additive manner to confer resistance. Studies have shown that such genes, when present individually, confer only intermediate resistance (Waldron et al, 1999;Stack et al, 2002aStack et al, , 2002b. Accessions exhibiting an intermediate reaction could have a minor gene(s) for resistance, thus preventing extreme susceptibility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations